Clinical features of sleep disturbances in anxiety disorders of neurotic and organic genesis. - Liashchenko, Yu.V.; Yuryeva, L.M. (Medicni Perspektivi, 2021)
There is a bi-directional link between dyssomnia and psychological diseases. Sleep disorders can influence the severity of the underlying disease, complicate the process of treatment, and increase the risk of the recurrence further. Besides, there is an obvious dependence of the sleep disorder severity from the pathological anxiety. The aim of the research: to study clinical features and relationship of sleep disorders and anxiety in patients with anxiety disorders of neurotic and organic genesis. To achieve the objective, 120 patients with anxiety-depressive disorders, who were divided into 2 groups depending on the genesis of the disease were studied. The first group included patients with anxiety-depressive disorders, anxiety phobic disorder and generalized anxiety disorder. The second group included patients with emotionally labile and organic anxiety disorders. The research was done with the help of clinical-psychopathological method added with psychometric scales and with the method of statistical processing. According to the results, it was detected that the level of insomnia was reliably higher in patients with anxiety disorders of organic genesis than in the group of patients with neurotic disorders. After the analysis of the components of the pathological anxiety it was determined that the components of emotional discomfort and the assessment of the prospects of anxiety dominated in the group of neurotic genesis, but the asthenic and phobic components were more expressed in the group of patients with anxiety disorders of organic level. In addition, according to the results of the correlation analyses, it was determined the link of the degree of expression and the severity of insomnia. Understanding of the semantic character of the pathological anxiety and clinical display of sleeping disorders will give the possibility to create the relevant differential rehabilitation programs of the treatment of the patients with anxiety-depressive disorders with sleep disorders.